2018
DOI: 10.1096/fj.201801659r
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of pirfenidone in the sugen/hypoxia rat model of severe pulmonary hypertension

Abstract: Heightened pulmonary artery smooth muscle cell (PA‐SMC) proliferation and migration and dynamic remodeling of the extracellular matrix are hallmark pathogenic features of pulmonary arterial hypertension (PAH). Pirfenidone (PFD) is an orally bioavailable pyridone derivative with antifibrotic, antiinflammatory, and antioxidative properties currently used in the treatment of idiopathic pulmonary fibrosis. We therefore evaluated the efficacy of curative treatments with PFD in the sugen/hypoxia (SuHx) rat model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…15 In the Sugen-hypoxia model of PH and RV failure, pirfenidone (30 mg/kg/day by mouth three times a day for three weeks) reduced RV fibrosis, but whether the reduction in RV fibrosis was secondary to the reduction in pulmonary vascular resistance also observed in the study or direct effects of pirfenidone on the RV could not be concluded. 22 Our results suggest that the reduction in RV fibrosis after pirfenidone treatment in the Sugen-hypoxia model may be explained primarily by the RV afterload reduction, as we did not observe any direct effects of pirfenidone treatment on RV fibrosis in our model of isolated RV failure. The lower absolute volume of fibrosis in the septum and the trend towards lower volume of LV fibrosis in the PTB rats after pirfenidone treatment observed in this study reflect lower volumes of the septum and LV in the PTB þ pirf rats compared with the non-treated PTB rats, as there was no difference in the volume fraction of fibrosis between the groups.…”
Section: Effects Of Pirfenidonesupporting
confidence: 47%
See 2 more Smart Citations
“…15 In the Sugen-hypoxia model of PH and RV failure, pirfenidone (30 mg/kg/day by mouth three times a day for three weeks) reduced RV fibrosis, but whether the reduction in RV fibrosis was secondary to the reduction in pulmonary vascular resistance also observed in the study or direct effects of pirfenidone on the RV could not be concluded. 22 Our results suggest that the reduction in RV fibrosis after pirfenidone treatment in the Sugen-hypoxia model may be explained primarily by the RV afterload reduction, as we did not observe any direct effects of pirfenidone treatment on RV fibrosis in our model of isolated RV failure. The lower absolute volume of fibrosis in the septum and the trend towards lower volume of LV fibrosis in the PTB rats after pirfenidone treatment observed in this study reflect lower volumes of the septum and LV in the PTB þ pirf rats compared with the non-treated PTB rats, as there was no difference in the volume fraction of fibrosis between the groups.…”
Section: Effects Of Pirfenidonesupporting
confidence: 47%
“…The study by Poble et al also demonstrated increased FoxO1 expression in lung tissue from both PAH patients and SuHx rats after pirfenidone treatment. 22 In this study, there was no effect of pirfenidone on RV FoxO1 expression, suggesting a different regulation of FoxO1 in the RV compared with the lungs.…”
Section: Effects Of Pirfenidonementioning
confidence: 47%
See 1 more Smart Citation
“…A trial evaluating combination treatment with the vasodilator sildenafil in patients with IPF and risk of PH is currently underway, although there is little evidence of efficacy for pirfenidone in the treatment of human pulmonary vascular disease (Behr et al, 2018). The drug is associated, however, with protection against pulmonary vascular remodelling and cardiac fibrosis in the rat Sugen/hypoxia model, although there was no change reported in mean PA pressure (Poble et al, 2019). Intriguingly, the same investigators showed that in smooth muscle cells isolated from lungs of patients with idiopathic PAH, application of pirfenidone did result in positive regulatory transcriptional element changes consistent with protective factors again pulmonary vascular disease development.…”
Section: Antifibrotic Therapies and Effects On The Pulmonary Vasculaturementioning
confidence: 99%
“…In most clinical studies, myocardial fibrosis is quantified using late gadolinium enhancement, and histological proof of the validity of this concept is readily available (9). The list of drugs that concomitantly improve RV function and decrease fibrosis in experimental models is long and includes beta-adrenergic blockers (10), iloprost (11), p38 MAPK inhibition (12), pirfenidone (13), and nintedanib (14). In most of these studies, RV effects were partly mediated by a drug-induced decrease in pulmonary vascular resistance.…”
mentioning
confidence: 99%